Characterization of plasma-sprayed Y2O3 coating and investigation of its visual aspect change - Seok, Hyun-Kwang; Choi, Eun Young; Cha, Pil-Ryung; Son, Myung-Chan; Choi, Byoung Lyong (ELSEVIER SCIENCE SA, 2011)
Yttria (Y2O3) has been commonly used as a protective coating material because it has strong resistance to plasma erosion with reducing the amount of reaction products generated during the semiconductor/LCD fabrication process. We have investigated the visual aspect of the plasma-sprayed Y2O3 coating both experimentally and numerically to propose the process conditions proper for white Y2O3 coating. It was demonstrated that heating of the particle surface in oxygen deficient plasma jet core resulted in the reduction of coating materials associated with the formation of black spots, while the re-oxidation of reduced feed stock materials at long spray distance, where they were exposed to relatively lower temperature of plasma and abundant oxygen, caused the whitening of coating. Based on the results, we proposed a spray coating condition proper for reducing the black spots formed in protective Y2O3 ceramic coating. (C) 2010 Published by Elsevier B.V.
Keywords: THERMAL-CONDUCTIVITY; DIFFUSIVITY; CERAMICS; VELOCITY; JETS; AIR